2014
DOI: 10.2967/jnumed.114.145995
|View full text |Cite
|
Sign up to set email alerts
|

Toward Radioguided Surgery with β Decays: Uptake of a Somatostatin Analogue, DOTATOC, in Meningioma and High-Grade Glioma

Abstract: A novel radioguided surgery (RGS) technique for cerebral tumors using β − radiation is being developed. Checking for a radiotracer that can deliver a β − emitter to the tumor is a fundamental step in the deployment of such a technique. This paper reports a study of the uptake of 90 Y-DOTATOC in meningiomas and high-grade gliomas (HGGs) and a feasibility study of the RGS technique in these types of tumor. Estimates were performed assuming the use of a β − probe under development with a sensitive area 2.55 mm in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 24 publications
(20 reference statements)
2
57
0
Order By: Relevance
“…This is indeed the level of agreement of the predictions close to the skin and on the tumor bulk. This assessment strengthens the feasibility studies on meningioma, glioma and neuro-endocrine tumors already published [9,10].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is indeed the level of agreement of the predictions close to the skin and on the tumor bulk. This assessment strengthens the feasibility studies on meningioma, glioma and neuro-endocrine tumors already published [9,10].…”
Section: Discussionsupporting
confidence: 82%
“…Although on meningioma there could be larger SUVs (reaching also values > 6, see Ref. [9]), the uptake was rated sufficient to test the technique, in particular in an ex-vivo (i.e. background free) environment.…”
Section: Patient Treatment Protocolmentioning
confidence: 96%
“…Previous studies have demonstrated the applicability of such a technique exploiting 90 Y-labeled peptides as a radiotracer in cases of meningioma and high-grade glioma (6). This paper represents the extension of those studies to NETs.…”
Section: Discussionmentioning
confidence: 94%
“…Heute et al used 68 Ga-DOTATOC to allow a pre-therapeutic assessment of patients with high grade glioma (HGG) undergoing a treatment with 90 Y-DOTATOC [73]. In a population including 11 patients with meningioma and 12 with HGG, Collamati et al [16] evaluated a possible approach to RGS with b -emitters. As concerning meningioma, all patients, but one with an atypical extracranial tumor, showed high uptake of 68 Ga-DOTATOC, with a TBR greater than 10 in almost all cases and usually above 20.…”
Section: Brain Tumorsmentioning
confidence: 99%
“…With respect to the specific type of detected radiation, they can be divided in g probes, the only ones widely diffuse in the surgical practice b -probes, and PET probes, detecting radiations originating from positron emitters [14][15][16][17][18].…”
Section: Detection Probe Systemsmentioning
confidence: 99%